The book of CSS3 : a developer's guide to the future of web design - Gasston, Peter (No Starch Press, 2015)
This completely updated second edition distills the dense technical language of the CSS3 specification into plain English and shows you what CSS3 can do now, in all major browsers. You'll find fully revised coverage of the updated syntax of gradients, grids, and flexible box layout, as well as all-new chapters on values and sizing, and graphical effects like filter effects and blend modes. With an abundance of real-world examples and a focus on the principles of good design, learn how to: style text with custom font choices, drop shadows, and other effects; create, position, and resize background images on the fly; spice up static Web pages with event-driven transitions and animations; apply 2D and 3D transformations to text and images; use linear and radial gradients to create smooth color transitions; take control of layout with grids, columns, and flexible alignment; and tailor a website's appearance to every type of Web-capable device. --